The Influence of Compensation on Employee Performance with Job Satisfaction as an Intervening Variable (A Case Study of PT. Angkasa Pura I Juanda) - Salsabila, Usva Nadhifah; Irawati, Sandra; Fuadiputra, Iqbal Ramadhani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research aims to find out employee performance, compensation, and job satisfaction, the direct influence of compensation on employee performance, the direct influence of compensation on employee job satisfaction, the influence of job satisfaction on employee performance and the indirect influence of compensation on employee performance through job satisfaction as an intervening variable. The type of research in preparing this thesis is explanatory research. The population in this research is employees of PT Angkasa Pura I Juanda, especially the airport security screening section, 304 employees. The data analysis method uses a range of scales and path analysis. Based on the results of the research and discussions that have been carried out, it can be concluded that employee performance is in the sufficient category, compensation is in the sufficient category, and employee job satisfaction is in the sufficient criteria. Compensation has a direct effect on employee performance, compensation has a direct effect on employee job satisfaction, job satisfaction has an effect on employee performance and compensation indirectly has an effect on employee performance through job satisfaction as an intervening variable.